2017
DOI: 10.5114/wo.2017.70111
|View full text |Cite
|
Sign up to set email alerts
|

The importance of serum and pleural fluid level of vascular endothelial growth factor (VEGF) and VEGF fluid/serum ratio in the differential diagnosis of malignant mesothelioma-related pleural effusion

Abstract: Aim of the studyVascular endothelial growth factor (VEGF) is one of the parameters that has been studied in differential diagnosis of malignant fluids. This study is aimed at evaluate applicability of serum, fluid VEGF level and fluid to serum VEGF ratio in the diagnosis of malignant pleural mesothelioma (MPM).Material and methodsThe patients with pleural effusion over age of 18, between 2011 and 2015 were included in the study. They were divided into three groups: group 1 – mesothelioma patients; group 2 – ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 19 publications
2
6
0
Order By: Relevance
“…Besides, there was a variation of significance in PF VEGF level among the three etiologies of benign exudative effusion (Parapneumonic, Tuberculosis and Empyema), however in case of heart failure and hepatic hydrothorax it has a non-significant changes between them (Table 3) In concordance with results of former studies, malignant and para-pneumonic pleural effusions recorded a higher PF VEGF levels than that found in pleural effusion due to heart failure [24,30,31]. Düzkoprü et al [16] results of their study revealed PF VEGF mean value was 3359 ±700 pg/ml in mesothelioma patients, 2175 ±435 pg/ml in nonmesothelioma patients, and 1092 ±435 pg/ml in bengin exudate group, accordingly it was concluded that, in mesothelioma group VEGF mean value was the highest than that observed in the benign exudative group with a statistically significant difference. In contrary to our study, Thickett and colleagues [5] noted lower mean values of VEGF in malignant diseases than in empyema.…”
Section: Introductionsupporting
confidence: 68%
See 3 more Smart Citations
“…Besides, there was a variation of significance in PF VEGF level among the three etiologies of benign exudative effusion (Parapneumonic, Tuberculosis and Empyema), however in case of heart failure and hepatic hydrothorax it has a non-significant changes between them (Table 3) In concordance with results of former studies, malignant and para-pneumonic pleural effusions recorded a higher PF VEGF levels than that found in pleural effusion due to heart failure [24,30,31]. Düzkoprü et al [16] results of their study revealed PF VEGF mean value was 3359 ±700 pg/ml in mesothelioma patients, 2175 ±435 pg/ml in nonmesothelioma patients, and 1092 ±435 pg/ml in bengin exudate group, accordingly it was concluded that, in mesothelioma group VEGF mean value was the highest than that observed in the benign exudative group with a statistically significant difference. In contrary to our study, Thickett and colleagues [5] noted lower mean values of VEGF in malignant diseases than in empyema.…”
Section: Introductionsupporting
confidence: 68%
“…),and patients on medications (eg. : anticancer therapy or corticosteroids or antiinflammatory drugs) [16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This was statistically significant (p=0.01). A recent study also mentioned this relationship [27].Ökten et al reported that, 83% of the pleural effusion patients had MPM. This value was very similar to our results [28].…”
Section: P R E P R I N Tmentioning
confidence: 87%